Athlete Adaptations to High-Altitude Training: A Behavioral Analysis - Fallah Sharif , Saeedeh; Sepehr Rezaee , Parastoo; Naser Sheikholeslami , Zahra Sadat; Kazemi, Seyed Vahid; Sajadi Teroujeni, Seyyed Sajed (Health Nexus, 2022)
The objective of this study was to explore the behavioral adaptations of athletes to high-altitude training, focusing on their physiological, psychological, and performance strategies, as well as social and environmental factors influencing their training experiences. This qualitative study employed semi-structured interviews to gather in-depth insights from 30 athletes who had undergone high-altitude training for at least three months. Participants were selected through purposive sampling to ensure a diverse representation of sports disciplines and training experiences. The interviews were transcribed and analyzed using NVivo software, with thematic analysis employed to identify key patterns and themes. Data collection continued until theoretical saturation was achieved, ensuring comprehensive coverage of the athletes’ experiences. The analysis revealed four main themes: physiological adaptations, mental adaptations, performance strategies, and social and environmental factors. Physiological adaptations included increased lung capacity, enhanced oxygen uptake, higher hemoglobin levels, and improved muscle endurance. Mental adaptations involved enhanced mental resilience, effective stress management, and goal-setting strategies. Performance strategies highlighted the importance of high-intensity training, balanced nutrition, and the use of altitude simulation techniques. Social and environmental factors emphasized the role of peer and coach support, environmental adjustments, and logistical management in facilitating successful high-altitude training. High-altitude training requires athletes to adapt across multiple dimensions, including physiological, psychological, and environmental aspects. The findings underscore the importance of individualized training protocols, comprehensive support systems, and effective management of environmental factors. These insights contribute to a deeper understanding of the holistic impact of high-altitude training, providing valuable guidance for athletes, coaches, and sports scientists to optimize training outcomes and enhance athletic performance.